SUMOylation of synaptic and synapse‐associated proteins: An update. Issue 2 (5th July 2020) - Henley, Jeremy M.; Seager, Richard; Nakamura, Yasuko; Talandyte, Karolina; Nair, Jithin; Wilkinson, Kevin A.
Abstract: SUMOylation is a post‐translational modification that regulates protein signalling and complex formation by adjusting the conformation or protein–protein interactions of the substrate protein. There is a compelling and rapidly expanding body of evidence that, in addition to SUMOylation of nuclear proteins, SUMOylation of extranuclear proteins contributes to the control of neuronal development, neuronal stress responses and synaptic transmission and plasticity. In this brief review we provide an update of recent developments in the identification of synaptic and synapse‐associated SUMO target proteins and discuss the cell biological and functional implications of these discoveries. Abstract : In this Review, we highlight advances in the field of neuronal SUMOylation and discuss how SUMOylation regulates processes within pre‐ and post‐synapses. Enhanced SUMOylation of Na + channels increases conductance and SUMO‐modified collapsin response mediator protein 2 stabilizes Na + channel surface expression. DeSUMOylation of metabotropic glutamate receptors mGluR7 promotes internalization. At the post‐synapse, GluK2 activation leads to SUMOylation and internalization. mGluR activation leads to accumulation of Ubc9, but can also enhance SENP1 levels, likely leading to homeostatic SUMO modulation. Downstream effects include regulation of actin dynamics, increasing AMPA receptor expression and local translation. These findings provide new appreciation of the roles of SUMOylation in synaptic function and plasticity.